Political Corruption and Nigeria’s Foreign Image: A Critical Assessment - Idowu, Samuel Sunday; Ogunbiyi, Hauwa Oyinlola (Kashere Journal of Politics and International Relations, 2024)
Political corruption has been identified as one of many bane of the international image in Nigeria, Though the anti-corruption agencies such as the Economic and Financial Crime Commission (EFCC), Code of Conduct Bureau and Independent Corrupt Practices Commission (ICPC), are set up to tame this monster, cases of political corruption do appear unbaiting in Nigeria as they spring up almost every week and there has been virtually no regime without one or two striking corruption reportages among the serving elected or appointive public officers. This work examines the effects of corruption on Nigeria’s foreign image between the periods of 2007-2023. Ex-post-facto research design was adopted while primary data sourced from interviews was complimented with secondary sources and elite theory was used to underpin its analysis. The study revealed that both Yaradua and Buhari regimes exhibited corrupt attitudes despite promising otherwise leading to the denting of Nigeria’s image as manifested in unfriendly treatment of diaspora citizens, poor foreign investment and foreign aids attraction. The paper recommended that strong political institutions should be built through constitutional amendment and citizens and civil society organisations be more proactive amongst others.